Evaluasi Efektivitas Drainase Jalan Kusuma Bangsa dalam Mengatasi Intensitas Banjir Tahunan dan Strategi Mitigasi Genangan Air di Kabupaten Lamongan - Nur Azizah Affandy; Yuniar Eka Andhika (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
The increasing urban growth in Lamongan Regency, Indonesia, has led to various issues and challenges related to stormwater management and flood risk in Lamongan District, particularly along Kusuma Bangsa Street. This study aims to evaluate the drainage system on Kusuma Bangsa Street by analyzing the capacity of drainage channels using a hydrological and hydraulic analysis approach. Rainfall data with return periods of 2, 5, and 10 years were used to estimate flood discharge. The results indicate that the flood risk in the area has significantly increased, as most existing drainage channels are unable to accommodate the planned flood discharge. Poor maintenance and excessive waste accumulation in certain sections of the channels further reduce the drainage system’s capacity. This evaluation is crucial for formulating strategies to improve drainage channels, mitigate flood risk, and enhance the resilience of urban infrastructure in Lamongan District. Flood risk mitigation strategies for this road include redesigning critical drainage sections, implementing green infrastructure solutions to enhance water absorption and reduce surface runoff, and adopting a routine maintenance schedule. These measures are expected to provide a more sustainable approach to urban flood risk management and support the sustainable development of the region.